Universal moisture tester calibration setting for common oil-rapeseed - Silveira, Expedito Paulo; Costa, Gisela Kanaan (Pesquisa Agropecuaria Brasileira, 2014)
Bench tests were conducted throughout 1985 to standardize sample weight, compression thickness and correction factors for common oil-rapeseed (Brassica napus L. var. oleifera Metzg.) moisture test on SE 1015 Universal Moisture Tester (UMT). CTC 4 seed samples from the same seed lot weighing 20, 30, 40 and 50 g replicated ten-fold were compressed each 25 divisions (on micrometer wheel) from 0.650 to 0.175 inches on thickness scale to obtain moisture values. Regression and variance analysis results indicate the 20/0.300 to 20/0.175 sets as the adequate ones. Regarding the existent high correlation (r = 0.96) between the 40 moisture values, each 20 obtained from different seed lot on UMT (20/0.175 set used) and on official oven (105 ± 3oC during 24 h), were estimated through the equation E (y/x) = a + bx, the correction factors a = -4.424 and b = 0.745. Thus, it was possible to calculate the oven estimated moisture values, with the 0.5% confidence intervals (P < 0.05 and P < 0.01), for the samples and for each 0.5 UMT readings on the attached scale.